Brain interstitial oligomeric amyloid β increases with age and is resistant to clearance from brain in a mouse model of Alzheimer's disease. Issue 8 (2nd May 2013) - Takeda, Shuko; Hashimoto, Tadafumi; Roe, Allyson D.; Hori, Yukiko; Spires‐Jones, Tara L.; Hyman, Bradley T.
Abstract : There is a growing body of evidence that soluble oligomeric forms of amyloid β (Aβ) play a critical role in Alzheimer's disease (AD). Despite the importance of soluble Aβ oligomers as a therapeutic target for AD, the dynamic metabolism of these Aβ species in vivo has not been elucidated because of the difficulty in monitoring brain Aβ oligomers in living animals. Here, using a unique large pore‐sized membrane microdialysis, we characterized soluble Aβ oligomers in brain interstitial fluid (ISF) of awake, freely moving APP/PS1 transgenic and control WT mice. We could detect high‐molecular‐weight (HMW) and low‐molecular‐weight (LMW) Aβ oligomers in the brain ISF of living animals, which increased dramatically in an age‐dependent manner (5‐ to 8‐fold increase, 4 vs. 17‐18 mo). Notably, HMW Aβ decreased more slowly than other forms of Aβ after acute γ‐secretase inhibition [% decrease from the baseline (HMW vs. LMW) was 36.9 vs. 74.1% (Aβ40, P <0.05) and 25.4 vs. 88.0% (Aβ42, P <0.01)], suggesting that HMW Aβ oligomers clear more slowly than other forms from the brain. These data reveal the dynamic metabolism of neurotoxic Aβ oligomers in AD brain and could provide new insights into Aβ‐targeted therapies for AD.—Takeda, S., Hashimoto, T., Roe, A. D., Hori, Y., Spires‐Jones, T. L.and Hyman, B. T., Brain interstitial oligomeric amyloid β increases with age and is resistant to clearance from brain in a mouse model of Alzheimer's disease. FASEB J. 27, 3239–3248 (2013). www.fasebj.org